Clinical Decision Making in Skilled Nursing/Long-Term Care: Using and Generating Evidence in the Field - Jeng, Heather (Seminars in Speech and Language, 2015)
In this article, setting-specific challenges and recent ethical concerns relating to speech-language pathology service provision in skilled nursing/long-term care are discussed in the context of implementing evidence-based practice (EBP). The American Speech-Language-Hearing Association's four-step EBP process is reviewed, and barriers to and limitations of EBP are considered. Resources established by experts in various domains for accessing and efficiently evaluating evidence are provided. Guiding principles of medical ethics are reviewed as foundational elements of patient-centered care, and systematic treatment design practices are offered as means of generating practice-based evidence, which allows for assessment of intervention efficacy and complements the EBP process. Last, the integration of all steps of the EBP model is illustrated in a case study of a patient with moderate to severe hypokinetic dysarthria and comorbidities. It is hoped that these resources, principles, and practices will be of use to clinicians specifically in the skilled nursing facility/ long-term care setting in the provision of high-quality speech-language pathology interventions.
Keywords: Evidence-based practice (EBP); practice-based evidence (PBE); hypokinetic dysarthria; skilled nursing; long-term care